THE MECHANISM OF DEVELOPING INFORMATION SORTING COMPETENCE IN FUTURE PEDAGOGUES - Azimova Odinakhan Abduqadir kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In this article, we should not forget that educational technologies and reforms carried out on a global scale within the framework of the activities of pedagogues will be the basis for the tomorrow of every society. In the educational practice of developed countries, special attention is paid to the concept of competence and it is recognized as a central, unique "node" concept of the educational process. and recommendations are given.